Conductive and Stretchable Adhesive Electronics with Miniaturized Octopus‐Like Suckers against Dry/Wet Skin for Biosignal Monitoring. (9th November 2018) - Chun, Sungwoo; Kim, Da Wan; Baik, Sangyul; Lee, Heon Joon; Lee, Jung Heon; Bhang, Suk Ho; Pang, Changhyun
Abstract: High adhesion and water resistance on skin surfaces are highly demanded properties for wearable and skin‐attachable electronics in various medical applications. Here, stretchable electronics with octopus‐like patterns (OPs) imprinted on a carbon‐based conductive polymer composite (CPC) film are presented. The bioinspired conductive suckers with dome‐like architectures are successfully exploited to sustain weight (500 g) in underwater, wherein this performance is known to be challenging. In addition, the artificial patch allows highly adhesive capabilities under both dry and wet conditions on various surfaces such as silicon (max. 5.24 N cm −2 ) and skin replica (max. 1.89 N cm −2 ) without contamination after detachment with an effortless peel‐off technique. The resulting device with low volumetric ratio of conductive carbon black presents sensitive and reliable piezoresistive responses to lateral strain and vertical pressure. By controlling the ratio of the carbon nanoplatelets in the polymeric matrix, electronic patch demonstrates both detection of electrocardiogram (ECG) and bending motions of wrist in dry and wet environments. Based on the characteristics shown in this work, the proposed electronic patch is a promising approach to realize wearable and skin‐attachable sensor devices for in vitro and in vivo monitoring of various biosignals. Abstract : Skin‐attachable and water‐resistant stretchable electronics are fabricated by employing an array of octopus‐like patterns on conductive polymer composite films. The electronic patch is not only highly sensitive to strain and pressure, but also strongly adhesive on dry and wet surfaces due to the suction effect. Finally, the device demonstrates measurements of biosignals and bending motions in underwater environments.